Elevated Glycated Hemoglobin Is Associated With Liver Fibrosis, as Assessed by Elastography, in a Population‐Based Study of Mexican Americans. Issue 12 (31st October 2020) - Watt, Gordon P.; De La Cerda, Isela; Pan, Jen‐Jung; Fallon, Michael B.; Beretta, Laura; Loomba, Rohit; Lee, Miryoung; McCormick, Joseph B.; Fisher‐Hoch, Susan P.
Abstract : Diabetes is associated with liver disease and risk of hepatocellular carcinoma. In this study, we evaluated the association between liver fibrosis measured by transient elastography and four glucose metabolism measures in the Cameron County Hispanic Cohort, a population‐based, randomly selected cohort of Mexican American Hispanics with high rates of diabetes and liver cancer. We measured liver fibrosis (a risk factor for hepatocellular carcinoma) in 774 well‐characterized cohort participants using transient elastography. We evaluated the association of liver fibrosis with glycated hemoglobin (HbA1c), fasting blood glucose, insulin, and insulin resistance using multivariable linear regression models. In multivariable models, log‐transformed HbA1c had the strongest association with liver fibrosis (β = 0.37, 95% confidence interval [CI] 0.04‐0.69, P = 0.038), after controlling for waist circumference, aspartate aminotransferase, alanine aminotransferase, liver fat, and other known confounders. The association was statistically significant among women (β = 0.33, 95% CI 0.10‐0.56, P = 0.009) and similar but nonsignificant among men (β = 0.41, 95% CI −0.17 to 0.98, P = 0.593). Waist circumference, platelet count, aspartate transaminase, and liver steatosis were each associated with liver stiffness. Conclusions: Elevated HbA1c is associated with liver fibrosis, a key risk factor for HCC, particularly among women. Our results indicate that Mexican Americans with uncontrolled HbA1c may benefit from routine screening by liver elastography to identify individuals at risk of liver disease progression.